Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0083668
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of Reading Intervention: A Systematic Review and Activation Likelihood Estimate Meta-Analysis

Abstract: A growing number of studies examine instructional training and brain activity. The purpose of this paper is to review the literature regarding neuroimaging of reading intervention, with a particular focus on reading difficulties (RD). To locate relevant studies, searches of peer-reviewed literature were conducted using electronic databases to search for studies from the imaging modalities of fMRI and MEG (including MSI) that explored reading intervention. Of the 96 identified studies, 22 met the inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 128 publications
(230 reference statements)
6
98
0
3
Order By: Relevance
“…The brain regions identified in this study were also consistent with those identified in several functional neuroimaging studies investigating the relationship of SES with early reading skills (Noble et al 2006; Raizada et al 2008). In addition, increased activation in these regions has been observed after reading intervention in children and adults with reading difficulties (Barquero et al 2014; Hoeft et al 2007; Richards and Berninger 2008; B. A. Shaywitz et al 2004; Temple et al 2003), which indicates the importance of these regions in learning to read and in reading remediation.…”
Section: Discussionmentioning
confidence: 92%
“…The brain regions identified in this study were also consistent with those identified in several functional neuroimaging studies investigating the relationship of SES with early reading skills (Noble et al 2006; Raizada et al 2008). In addition, increased activation in these regions has been observed after reading intervention in children and adults with reading difficulties (Barquero et al 2014; Hoeft et al 2007; Richards and Berninger 2008; B. A. Shaywitz et al 2004; Temple et al 2003), which indicates the importance of these regions in learning to read and in reading remediation.…”
Section: Discussionmentioning
confidence: 92%
“…Increased activation in less skilled readers has been attributed to overengagement, due to increased difficulty and effort necessary during reading tasks (Shaywitz et al 1998;Brunswick et al 1999;Milne et al 2002). This compensatory theory is supported by findings of more prominent hyperactivation in older, or remediated, readers (Shaywitz et al 2003;Hoeft et al 2011;Richlan et al 2011;Barquero et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…52 There are, however, relevant examples from reading and language interventions with older children. 55,56 Even without this neuroimaging evidence, the extant findings from behavioral studies are impressive and persuasive with regard to the benefits of high-quality preschool education. For example, several studies have demonstrated that high-quality early education is associated with significant gains on measures of neurocognitive ability, such as executive function, greater skill in perspective taking (or theory of mind), the ability to regulate attention in response to emotional stimuli, and speed of information processing.…”
Section: Opportunities For Repairmentioning
confidence: 99%